Heterogeneous nitrogen fixation rates confer energetic advantage and expanded ecological niche of unicellular diazotroph populations - Masuda, Takako; Inomura, Keisuke; Takahata, Naoto; Shiozaki, Takuhei; Sano, Yuji; Deutsch, Curtis; Prášil, Ondřej; Furuya, Ken (Communications biology, 2020)
Nitrogen fixing plankton provide nitrogen to fuel marine ecosystems and biogeochemical cycles but the factors that constrain their growth and habitat remain poorly understood. Here we investigate the importance of metabolic specialization in unicellular diazotroph populations, using laboratory experiments and model simulations. In clonal cultures of Crocosphaera watsonii and Cyanothece sp. spiked with 15N2, cellular 15N enrichment developed a bimodal distribution within colonies, indicating that N2 fixation was confined to a subpopulation. In a model of population metabolism, heterogeneous nitrogen (N2) fixation rates substantially reduce the respiration rate required to protect nitrogenase from O2. The energy savings from metabolic specialization is highest at slow growth rates, allowing populations to survive in deeper waters where light is low but nutrients are high. Our results suggest that heterogeneous N2 fixation in colonies of unicellular diazotrophs confers an energetic advantage that expands the ecological niche and may have facilitated the evolution of multicellular diazotrophs.
Keywords: energetický metabolismus; Cyanobacteria; Ecosystem; Nitrogen; Computer Simulation; Adaptation, Physiological; biologická evoluce; Cyanothece; fyziologická adaptace; sinice; Models, Biological; Nitrogen Fixation; Energy Metabolism; biologické modely; Biological Evolution; dusík; fixace dusíku; ekosystém; počítačová simulace